Development of a wireless charging system for consumer electronics - Goh, Amos Zhi Zhong (2017)
Wireless power transfer has progressed significantly in the recent years especially the near-field non-radiative power transfer. This is due to the high demand of the consumer electronics. Inductive coupling method that has existed for more than a few decades it is a well-understood method for wireless power transfer, but it's working principle suffers a few critical disadvantage such as the low degree of misalignment between coils. Hence in this report, magnetic resonant coupling method will serve as an alternative coupling method to address the inductive coupling disadvantage. This report covers the fundamentals of wireless charging technology and detailed explanation of every single circuitry design of the wireless charging system. The system includes the DC/AC Royal Oscillator, parallel resonant circuit, AC/DC rectifier, DC/DC converter. In the result and discussion, the comparison between the inductive coupling and magnetic resonant coupling shows that magnetic resonant coupling is able to transmit at a larger distance and is almost immune to any stray interference. The well-known dual peak resonance phenomenon is also tested and discussed in this report. The final prototype of the wireless charging system has tested and demonstrated to be able to transmit power wirelessly at a distance of 2 inches with more than 7W. All these results match with the literature review theories.